Sound Intensity of a Drum - Ticha Sethapakdi (International Scholastic Journal of Science, 2012)
A small steel ball was dropped onto the center of a bongo drum. The relationship between impact energy and the maximum amplitude of the sound produced upon impact was determined using release heights ranging from 5 to 70 cm. It was found that there was a power relation between the impact energy and the maximum amplitude of the sound, indicating that the partitioning of energy in the system is dependent on impact energy.